ANALISIS PRODUKSI GAS HIDROGEN MELALUI METODE ELEKTROLISIS AIR DENGAN KATALISATOR KOH - Sekar Alfitasari Widodo (2023)
Hydrogen gas is an alternative fuel that can be obtained through the method of electrolysis of water, using a catalyst of KOH compounds. The electrolysis method uses the highest KOH concentration of 13.3% and produces a volume of hydrogen gas 610.8 mL, a concentration gas hydrogen 84.35 ppm, and a highest hydrogen energy (BTU) of 7.010 BTU with power 85.26 Watt. The hydrogen gas will be inserted into the combustion chamber and will be mixed with pertalite through the Manifold Inlet method. The best SFC (Specific Fuel Consumption) result is having a SFC value of 0.51375 (Kg/kWh) at an electrolysis power of 85.26 Watt.